Rethinking turning points: trajectories of parenthood and desistance - Schinkel, Marguerite (2019)
Purpose: While much research has examined the role of parenthood in desistance, it has largely treated parenthood as a binary condition. This article examines the interaction between trajectories of parenthood and trajectories of desistance in order to understand how these interact over time. Methods: This article is based on life story interviews with 29 men and women in Scotland who had experienced repeated short-term imprisonment and mentioned children as significant in their lives, ten of whom were interviewed again 2 years later. Results: While becoming pregnant was a (very) positive turning point for many of the women, trauma surrounding parenthood through pregnancy loss, lack of conception and losing the parental role had a clear negative effect on trajectories of desistance.Men had similar experiences, although pregnancy was only a turning point for them if they felt their partner was not fulfilling their role as mother-to-be. Conclusion: A more nuance understanding of the lives of people processed by the criminal justice system is needed, looking beyond their interactions with the criminal justice system and not only in relation to parenthood but also with regard to other frequently cited 'turning points' such as work and relationships